Fabrication of ZnO periodic structures by 3D printing. Issue 14 (November 2016) - Tubío, Carmen R.; Guitián, Francisco; Gil, Alvaro
Abstract: In this study, aqueous colloidal ZnO inks with tailored rheological properties have been developed for 3D printing of periodic structures. These periodic structures consisting of alternating layers with tetragonal symmetries were fabricated by extrusion of ZnO inks with concentration of 48 vol%. The as-prepared structures had well-defined and interconnected layers with rod diameters of 200 μm. The inks exhibited pseudoplastic behaviour and were in accordance with the power-law model. Oscillatory and creep-recovery measurements indicated that the inks had the appropriate viscoelastic behaviour and excellent printing characteristics. In order to acquire a high mechanical strength, the structures were sintered at various temperatures between 900 and 1500 °C, and their compressive strength was evaluated. The results indicated that 1500 °C was an optimum sintering temperature to obtain structures with high compressive strength up to 11.09 MPa. The reported ZnO inks offer multiple possibilities for the fabrication of novel structures for practical applications.